ANALISIS DAYA DUKUNG EKONOMI DAERAH TERHADAP PENGEMBANGAN KAWASAN INDUSTRI KABUPATEN BANGKALAN - Sutjipto Ngumar; Hening Widi Oetomo (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2007)
In the development of industrial area, the first step needed is to find out about the current conditional supportiveness on the smallest area unit. In terms of Regency or Municipality, its smallest unit is Subdistrict. The setting of this study is Bangkalan Regency while its smallest area units studied are the Subdistricts of Kamal, Labang, Kwanyar, Modung, Tanah Merah, Tragah, Socah and Burneh. Why these Subdistricts are chosen is because of their common access from Kamal harbor and Suramadu Bridge. The method used is SWOT analysis which considering internal factor constructed in IFAS (Internal Strategic Factor Analysis Summary) table and external factor constructed in EFAS (External Strategic Factor Analysis Summary) table.The highest IFAS values are Kamal’s and Modung’s, while EFAS values are assumed to be equal because the competitors condition are relatively similar. Based on IFAS and EFAS values, the quadrant position will be derived in SWOT matrix whose x axis is IFAS and y axis is EFAS. There are 4 quadrants in SWOT matrix, they are S-O (Strengths – Opportunities), W-O (Weakness – Opportunities), S-T (Strengths - Threats), and W-T (Weakness – Threats). The results of this current study suggest that from 8 Subdistricts we studied, there are 7 (seven) Subdistricts in S-O quadrant and 1 (one) in W-O quadrant. Based on the position of these subdistricts in SWOT quadrant, the appropriate strategy for each Subdistrict in developing their area in order to support the development of industrial area will be determined.